2003
DOI: 10.1021/jm030776l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships ofcis-Tetrahydrophthalazinone/Pyridazinone Hybrids:  A Novel Series of Potent Dual PDE3/PDE4 Inhibitory Agents

Abstract: In this study, the synthesis and in vitro and in vivo pharmacological investigations of a new series of phthalazinone/pyridazinone hybrids with both PDE3 and PDE4 inhibitory activities are described. These compounds combine the pharmacophores of recently discovered 4a,5,8,8a-tetrahydro-2H-phthalazin-1-one-type inhibitors of PDE4 and the well-known 2H-pyridazin-3-one-type PDE3 inhibitors such as the tetrahydrobenzimidazoles. Most of the synthesized compounds are pharmacologically spoken PDE3/PDE4 hybrids. All h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…By measuring albumin in lavage or in tissue, we could clearly see a close correlation between inflammation and albumin concentration. Experimental lung edema and clinical lung edema can evidently be attenuated by selective PDE3 inhibition (44) and/or PDE4 inhibition (39,44,(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…By measuring albumin in lavage or in tissue, we could clearly see a close correlation between inflammation and albumin concentration. Experimental lung edema and clinical lung edema can evidently be attenuated by selective PDE3 inhibition (44) and/or PDE4 inhibition (39,44,(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Given the success of the combination of β 2 agonists as bronchodilatory drugs and inhaled glucocorticosteroids as anti-inflammatory drugs in the treatment of patients with asthma and in some COPD patients, a number of research groups have attempted to develop dual PDE3/4 inhibitors as single molecules that possess bifunctional bronchodilatory and anti-inflammatory activity. Researchers at the Leiden/Amsterdam Center for Drug Research have reported the synthesis and structure activity relationship of a series of potent dual PDE3/4 inhibitors which are able to inhibit arachidonic acid-induced ear edema in the mouse, achieving 44% inhibition at an oral dose of 16 mg/kg [95]. …”
Section: Clinical Datamentioning
confidence: 99%
“…Recently, these derivatives have been reported as potent hepatoprotective agents 6 , antibacterial and antifungal agents 7 , COX-2 inhibitors 8 , platelet aggregation inhibitor [9][10][11][12] , phosphodiesterase 13,14 . They also act as cytotoxic (cell-killing) agents and antihormonal drugs, which reduce the proliferation of the tumors [15][16] . The sulfonamides constitute an important class of drugs, with several types of pharmacological agents possessing antibacterial 17 , anti-carbonic anhydrase 18,19 , diuretic 18,20 , hypoglycemic 21 , antithyroid 22 , and antiprotons activities [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%